Generation jobless : youth unemployment (2013)
Posits that countries that make the investment and choices needed to grapple with their unemployed youth viz., ignite growth, break down cartels and build bridges between education and work, could see some dramatic improvement ahead.
Keywords: UNEMPLOYMENT